Introduction to the dossier - Carrillo, Ana María (Sekkan Revista de Ciencias Sociales y Humanidades, 2026)
In 1918, four years after the Great War had begun, an influenza pandemic started its journey across the world. In the story Pale Horse, Pale Rider, by Catherine Ann Porter, first published by The Southern Review in 1939, the writer describes the frustrated love story of a journalist and a soldier who fall ill during the influenza pandemic; she loses consciousness and, upon recovering it, learns that the young man has died. The final lines of the story point to the impact that the global armed conflict and sanitary disaster left on those who survived them: “No more war, no more plague, only the dazed silence that follows the ceasing of the heavy guns; noiseless houses with the shades drawn, empty streets, the dead cold light of tomorrow. Now there would be time for everything” (Porter, 196: 165).1Incidentally, this was not only the case of the protagonist, but also that of Porter herself, who worked as a reporter for a Denver newspaper during the war and was one of the people struck by influenza. It is said that her relatives had already arranged the preparations for her burial and written her obituary when, inexplicably, she showed signs of life and later recovered (Unrue cited by Brooker, 2009: 214). The writer would later say: “The plague of influenza simply divided my life, cut it across like that” (Porter cited by Brooker, 2009: 215).2For a disease to become epidemic and, even more so, pandemic means that this individual tragedy is repeated thousands, hundreds of thousands, or, as in this case, millions of times, thereby altering the economic, political, social, and cultural structure of a society. That is why it was strange that so little had been written about this pandemic. As historian Alfred W. Crosby points out, both in literature and in historiography, for a long time there was a kind of collective amnesia regarding the influenza of 1918-1920, despite the fact that over the course of two years it infected one third of all the inhabitants of the Earth; more people died in it than in World War I and, depending on our age, they were our great-grandparents, great-great-grandparents, or great-great-great-grandparents, perhaps because it was difficult to articulate the trauma caused by the arrival of influenza at a time when the world’s population was expecting peace.